The upper gastrointestinal endoscopic and rectosigmoidoscopic findings in Behçet’s disease - M. Kadir AKSÖZ; Belkıs ÜNSAL; İlgül ZEREN and G. ÖNDER and N. EKİNCİ and Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-